2020
DOI: 10.1149/2162-8777/abb2b1
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Absorption Spectroscopy of Silicon Carbide Thin Films Improved by Nitrogen for All-Silicon Solar Cells

Abstract: Synchrotron-based experiments in combination with optical measurements were used to explore the potential of a photovoltaic material based on silicon carbonitride (SiCN) thin films, in particular for the use in space solar cells. The large bandgap, SiCN films were fabricated using electron cyclotron resonance plasma-enhanced chemical vapour deposition (ECR-PECVD) followed by low-temperature annealing processes. X-ray absorption near edge structure (XANES) with excitations at the carbon, nitrogen, and silicon K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…For the simulated XANES spectrum for N C (Figure (d)) , three main peaks are observed at 401.5, 405.4, and 420.0 eV, which is very similar to the experimental results for XANES of an N–Si structure (Figure (a)). For the simulated results, the main peak at 405.4 eV is related to π* state transitions of Si–N bond, while the peak at 420 eV is attributed to the σ* state transitions . This result is in good agreement with a previous study focused on N C sites in SiC. ,, Accordingly, we conclude that SiNx is attributed to N C .…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…For the simulated XANES spectrum for N C (Figure (d)) , three main peaks are observed at 401.5, 405.4, and 420.0 eV, which is very similar to the experimental results for XANES of an N–Si structure (Figure (a)). For the simulated results, the main peak at 405.4 eV is related to π* state transitions of Si–N bond, while the peak at 420 eV is attributed to the σ* state transitions . This result is in good agreement with a previous study focused on N C sites in SiC. ,, Accordingly, we conclude that SiNx is attributed to N C .…”
Section: Resultssupporting
confidence: 90%
“…For the simulated results, the main peak at 405.4 eV is related to π* state transitions of Si–N bond, while the peak at 420 eV is attributed to the σ* state transitions . This result is in good agreement with a previous study focused on N C sites in SiC. ,, Accordingly, we conclude that SiNx is attributed to N C .…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Conversely, for ceramic materials 3D printed with PLAc 103 ‐CTA, the pronounced peak at 1845 eV indicates a greater prevalence of Si‐C geometries. [ 32a,33 ] C K‐edge NEXAFS provided further structural information on the ceramic materials from the perspective of C atoms (Figure 3B). The spectra exhibited features at energies between 284.3 to 299.7 eV (Table S6, Supporting Information), which were attributed to the transitions of C 1s orbitals to σ* occur from sp 3 bonded C. [ 32,34 ] The peak fitting analysis of C K‐edge NEXAFS (Figure S21A–E, Supporting Information) revealed that the PLAc‐CTA X n plays a significant role in the formation of sp 2 bonded C atoms (284.3 eV, peak C1).…”
Section: Resultsmentioning
confidence: 99%